Association of the Somatostatin Analog Octreotide With Magnetic Nanoparticles for Intraocular Delivery: A Possible Approach for the Treatment of Diabetic Retinopathy - Amato, Rosario; Giannaccini, Martina; Dal Monte, Massimo; Cammalleri, Maurizio; Pini, Alessandro; Raffa, Vittoria; Lulli, Matteo; Casini, Giovanni (Frontiers in Bioengineering and Biotechnology, 2020)
The somatostatin analog octreotide (OCT) displays important neuroprotective and anti-angiogenic properties that could make it an interesting candidate to treat diabetic retinopathy (DR). Unfortunately, systemic drug administration is hindered by severe side effects, therefore topical administration routes are preferable. However, drug delivery through eye drops may be difficult due to ocular barriers and, in the long term, could induce ocular damage. On the other hand, intraocular injections must be repeated to maintain drug concentration, and this may cause severe damage to the eye. To decrease injection frequency, long-term release and reduced biodegradation could be obtained by binding the drug to biodegradable polymeric nanoparticles. In the present study, we made a preparation of OCT bound to magnetic nanoparticles (MNP-OCT) and tested its possible use as an OCT delivery system to treat retinal pathologies such as DR. In particular, in vitro, ex vivo and in vivo experimental models of the mammalian retina were used to investigate the possible toxicity of MNPs, possible effects of the binding to MNPs on OCT bioactivity, and the localization of MNP-OCT in the retina after intraocular injection. The results showed that, both in human retinal endothelial cells (HREC) and in mouse retinal explants, MNPs were not toxic and the binding with MNPs did not influence OCT antiangiogenic or antiapoptotic activity. Rather, effects of MNP-OCT were observed at concentrations up to 100-fold (in HREC) or 10-fold (in mouse retinal explants) lower compared to OCT, indicating that OCT bioactivity was enhanced in MNP-OCT. MNP-OCT in mouse retinas in vivo after intraocular delivery were initially localized mainly to the outer retina, at the level of the retinal pigment epithelium, while after 5 days they were observed throughout the retinal thickness. These observations demonstrate that MNP-OCT may be used as an OCT intraocular delivery system that may ensure OCT localization to the retina and enhanced OCT bioactivity. Further studies will be necessary to determine the OCT release rate in the retina and the persistence of drug effects in the long period.